Development interactive learning multimedia in improving children's beginning reading skills - Rihana, Rihana; Dhieni, Nurbiana; Nurjannah, Nurjannah (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The development of digital technology demands the education world to adapt in creating learning processes that are innovative, engaging, and effective. However, in reality, the learning process in many schools is still dominated by conventional methods that tend to be teacher-centered, making them less able to accommodate the diverse learning needs of students. The low ability of students in certain aspects (for example: critical thinking, conceptual understanding, or literacy) is a problem often encountered in the field. This is caused by the lack of use of interactive and contextual learning media, resulting in students being less actively involved in the learning process. The existing learning media do not align with the curriculum and the learning needs of the students. The population in the study consisted of 3 schools totaling 60 students. The sampling technique is purposive sampling. Data analysis was carried out in a qualitative descriptive and quantitative descriptive manner. The results of the study are as follows. Multimedia Development of Interactive Learning There are several media in it, namely text, audio, visual, color, and animation and Multimedia interactive learning can improve children's early reading ability. The average score of the pretest was 70.7 and the average posttest was 95. It can be seen that the average score of children increased by 26% after using interactive learning multimedia. It was concluded that multimedia interactive learning can improve early childhood reading skills.